Espelhos negros: mutações do desejo e da crítica na comunicação - Trento, Francisco Beltrame (2017)
Contemporaneity is characterized by the interweaving of human beings with multiple media forms, through material mediatic objects (our black mirrors). Also by stimuli and incorporeal enunciates that are embodied by them, or in which they momentarily crystallize themselves. These dispositives and networks have been represented in the audiovisual field, scenic arts, performance and literature frequently. The television anthology Black Mirror (Channel Four, 2011-2014; Netflix, 2016-), one of the fictional guides in our analysis, is a set of narratives that, exacerbating this state of things, discusses how those media ecosystems are intrinsically linked with the production of desires in the individuals. We aim to identify and map those modulations through a Spinozist semiotic of affects. Among the affects, we have identified the production of a desire to control, a mode of existence or set of ideas that presupposes that we have the total control of situations and absolute truth through the same media dispositives that involves us. We relate that to the production of subjectivity of the standard ideal neurotypical human being, or of the fine products that emerges from the processes of the antropotecnical eugenic machine, studied by Fabian Ludueña. Starting from this point, we aim to focus the communication processes as agencements or encounters (occursus). Following Black Mirror’s narrative, we seek to produce a mediatic cartography of good and bad encounters, not constructed through moral systems, but following Spinoza’s ethical evaluation, mapping composition and decompositions, increases and decreases of potency observing the semiotical production of desires through affections. Besides the desire to control, which emerged from the anthropocentric and anthropotechnical crusade, other types of desires can be machined in the subjectivities engaged to the omnipresent media dispositives as part of the contemporaneous capitalist system, as the desire of emulation or the desire of imitation, explained in Spinoza's “definition of affects”. The difficult task is to think escapes or lines of flight to these types of media agencements that can emerge performatively/artistically by experimenting with the same media materialities or enunciative apparatuses (we don’t consider them neither good or evil but they can be (re) allocated in agencements that produce good or bad encounters in a field of immanence). It requires to look for the production of good encounters and active agency, or to think new possibilities of world construction. We consider that, in the presence of the exhaustion produced by the control systems, minor and apparently contingent gestures and artistic practices can resist to the total control and normativity. It’s through them that we advocate in favor of an immanent critique of media, incongruent to identitarian bubbles and politics – that usually target moral judgement without observing events’ causality network and the desires agenced in its nodes. Against that, we ally with the philosophy of Baruch Spinoza, Gilles Deleuze, Catherine Malabou and other contemporary rereadings of the Dutch philosopher that can relate with them, as the work of Brian Massumi. To discuss the emergent issues of those complex questions, and try to develop an immanent media critique, Brian Massumi and Erin Manning bring us their particular interpretations of immanent critique, performed through research-creation art practices and minor/disruptive gestures